The use of end-tidal capnography to monitor non-intubated patients presenting with acute exacerbation of asthma in the emergency department. - Howe, Teo Aik; Jaalam, Kamaruddin; Ahmad, Rashidi; Chew, Keng Sheng; Nik Ab Rahman, Nik Hisamuddin (2011)
STUDY OBJECTIVE